Conformity with Compulsive Buying in Adolescents - Jenita Aryani Dengah; M.K.P Abdi Keraf; Theodora Takalapeta (Journal of Health and Behavioral Science, 2021)
Compulsive buying is a shopping behavior that is repeated and has a strong urge to shop which is done as a diversion from negative feelings, such as stress and anxiety. Compulsive buying can be influenced by the social environment, where a person will behave following the expectations of others, the presence of pressure, or what is often called conformity. This study aims to determine the relationship between conformity and compulsive buying in adolescents. The approach used is a quantitative approach with the type of correlational research. The measuring instrument in this study uses conformity scale adaptation and compulsive buying scale adaptation. Respondents in this study were teenagers aged 18-24 years totaling 399 teenagers living in the city of Kupang. The results of hypothesis testing using the Spearman correlation technique obtained a correlation coefficient of 0.208 with a significance level of 0.000 (p <0.05). This means that H0 is accepted, that is, there is a positive and significant relationship between conformity and compulsive buying in adolescents in Kupang City.